In-service training needs of the faculty of Febias College of Bible - De Felipe, Aurea Vicente Bentillo 1948- (1986)
The author aimed to determine the in-service training needs of the faculty of FEBIAS College of Bible during School Year 1985-1986. She made use of the normative-descriptive method. A questionnaire was used as the research tool.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Vita.
Keywords: Febias College of Bible; Teachers -- In-service training